2022
DOI: 10.3389/fnagi.2022.945875
|View full text |Cite
|
Sign up to set email alerts
|

Selective Detection of Misfolded Tau From Postmortem Alzheimer’s Disease Brains

Abstract: Tau aggregates are present in multiple neurodegenerative diseases known as “tauopathies,” including Alzheimer’s disease, Pick’s disease, progressive supranuclear palsy, and corticobasal degeneration. Such misfolded tau aggregates are therefore potential sources for selective detection and biomarker discovery. Six human tau isoforms present in brain tissues and both 3R and 4R isoforms have been observed in the neuronal inclusions. To develop selective markers for AD and related rare tauopathies, we first used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 77 publications
(106 reference statements)
1
30
0
Order By: Relevance
“…Through our experimental study, we demonstrated that the E264G mutation (R1R3-GG) favors fibril formation, whereas the G326E mutation (R1R3-EE) forms disordered aggregates. Understanding the conformations of 3R isoforms could pave way to tune PiD specific ligands, which might help in the detection of Tau conformations similar to bithiophene-vinylene-benzothiazole (bTVBT4), which can detect the AD fold but not the PiD fold. With Tau pathogenesis suggested to occur on the surface of MT, the results described in this work share insights on the sequence-specific conformation of Tau protein paving the way to probe pathogenesis at a monomeric level. , Thus, our study exemplifies the importance of NH6 peptides, owing to their ability to tune the conformational properties of the PGGG motif and thus influence the VQ6 peptide downstream to it. The NH6 peptide also plays a significant role in understanding Tau–MT interactions, which might help in building therapeutics targeting the inter-repeat regions.…”
Section: Discussionmentioning
confidence: 58%
“…Through our experimental study, we demonstrated that the E264G mutation (R1R3-GG) favors fibril formation, whereas the G326E mutation (R1R3-EE) forms disordered aggregates. Understanding the conformations of 3R isoforms could pave way to tune PiD specific ligands, which might help in the detection of Tau conformations similar to bithiophene-vinylene-benzothiazole (bTVBT4), which can detect the AD fold but not the PiD fold. With Tau pathogenesis suggested to occur on the surface of MT, the results described in this work share insights on the sequence-specific conformation of Tau protein paving the way to probe pathogenesis at a monomeric level. , Thus, our study exemplifies the importance of NH6 peptides, owing to their ability to tune the conformational properties of the PGGG motif and thus influence the VQ6 peptide downstream to it. The NH6 peptide also plays a significant role in understanding Tau–MT interactions, which might help in building therapeutics targeting the inter-repeat regions.…”
Section: Discussionmentioning
confidence: 58%
“…Protein misfolding is one of the salient features of neurodegenerative diseases. Hyperphosphorylated and aggregated forms of Tau protein are found in the brains of patients with Alzheimer’s Disease ( Wu et al, 2022 ). Similarly misfolded and aggregated Alpha-Synuclein deposits are found in individuals with Parkison’s Disease and in Dementia with Lewy Bodies ( Sanderson et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, identification of p-tau198 or other promising candidates for general MCI diagnosis may have significant impact on clinical practice for much needed early AD biomarker development. Because of relatively small size of our cohorts, it will be interesting and important to further develop such biomarkers with a significantly large case number of clinical cohorts and with AD patient plasma samples in the future, incorporating ultrasensitive detection methods such as Single Molecular Array (Simoa) or Meso Scale Discovery Multi-Array technologies (MSD). , It will also be interesting to compare the sensitivity of different ultrasensitive detection methods, for example, misfolded protein-based amplification RT-QuIC technology versus p-tau aggregation-based Simoa tests.…”
Section: Discussionmentioning
confidence: 99%